Through a Shot Glass, Darkly: The Study of Games in the Light of Drinking Games. Issue 1 (January 2019) - Sotamaa, Olli; Stenros, Jaakko
Drinking games have a history several millennia long. Yet the global community of game scholars has barely touched drinking and games, leaving the area for researchers of health and safety issues. This article is a think piece that approaches drinking games as games and as play, ponders what the study of games can learn from drinking games, weighs what is at stake in them, and connects them to discussions in contemporary game studies relating to materiality, modding, and criticism of the idealization of play.